Response of conilon coffee (Coffea canephora Pierre ex Froehn.) plants to npk application in condensed planting system - Bragança, Scheilla Marina; Silva, Enilson Barros; Martins, André Guarçoni; Santos, Lucio Pereira; Lani, José Antônio; Volpi, Paulo Sérgio (Coffee Science - ISSN 1984-3909)
The response of plants to the application of fertilizer varies in function of diverse factors, among them we highlight the type of soil, dose of nutrient, and spacing used. Thus, the objective of this work was to evaluate the effect of NPK application in the production of Conilon coffee plants (Coffea canephora Pierre ex Forehn.), cultivated in different densities of planting. The studied were composed of four quantities of N (0, 150, 300 and 450 kg ha-1), four of P2O5 (0, 50, 100 and 150 kg ha-1), four of K2O (0, 150, 300 and 450 kg ha-1) and four densities of planting: 2,0 x 1,0 (5000 plants ha-1); 2,5 x 1,0 (4000 plants ha-1); 3,0 x 1,0 (3000 plants ha-1) and 3,0 x 1,5 m (2222 plants ha-1). It was used the experimental design in randomized blocks, being the treatment distributed in four blocks arranged in a factorial fractional (4 x 4 x 4)1/2 scheme. There was a reduction in the dose of nitrogen in relation to those normally recommended for the Conilon coffee plants. The potassium did not influence the production. The phosphorus increased the productivity; however, it was not possible to determinate the maximum economic dose. There were no interactions between the densities of planting and the level of NPK applied.